Handwriting Legibility and Its Relationship to Spelling Ability and Age: Evidence From Monolingual and Bilingual Children - Caravolas, Markéta; Downing, Cameron; Hadden, Catrin Leah; Wynne, Caspar (Frontiers in Psychology, 2020)
Studies of the relationship between spelling and handwriting concur that spelling skills influence the dynamic processes and fluency of handwriting. However, it remains unclear whether variations in spelling ability are related to variations in the legibility of handwriting, to what extent this relationship may be task- and language-specific, or how important spelling skills are relative to the amount of handwriting experience afforded by an individual’s age and number of years of schooling. We investigated these questions in a study comparing spelling and handwriting legibility in a group of N = 150 Welsh-English bilingual children matched in age and number of years of schooling to a group of N = 150 English-monolingual children, as well as to a group of N = 150 younger, English monolingual children matched to the bilingual group in spelling ability. All groups completed the Spelling and Handwriting Legibility Test (SaHLT) and a broader battery of literacy measures. The bilingual children were found to have poorer handwriting legibility than same age peers, and in some cases, than their younger, spelling-ability peers, suggesting that spelling ability, more so than amount of handwriting experience and years of schooling impacts handwriting legibility. This was corroborated in a series of multi-group path models, where all children’s handwriting was predicted by spelling ability more strongly than by age, and the effect of spelling generalized to an independent spelling task in all groups. Finally, bilingual children seemed to draw on general (Welsh) as well as orthography-specific (English) knowledge when handwriting in English.